2012
DOI: 10.1056/nejmoa1207363
|View full text |Cite|
|
Sign up to set email alerts
|

A Trial of Intracranial-Pressure Monitoring in Traumatic Brain Injury

Abstract: Background Intracranial-pressure monitoring is considered the standard of care for severe traumatic brain injury and is used frequently, but the efficacy of treatment based on monitoring in improving the outcome has not been rigorously assessed. Methods We conducted a multicenter, controlled trial in which 324 patients 13 years of age or older who had severe traumatic brain injury and were being treated in intensive care units (ICUs) in Bolivia or Ecuador were randomly assigned to one of two specific protoco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
703
3
24

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 1,109 publications
(746 citation statements)
references
References 18 publications
16
703
3
24
Order By: Relevance
“…Some practices, such as the use of hypothermia in TBI patients, decompressive craniectomy, and ICP monitoring, have been reported to lack efficacy at improving outcomes in preliminary clinical trials. [44][45][46] Nevertheless, our findings are in agreement with multiple observational studies suggesting that the development of specialized neurocritical care unitsusually supported by the presence of neurointensivists and utilizing evidence-based protocols-may contribute to improved patient outcomes. 28 International studies involving neurocritical care patients have suggested that there is considerable variability in outcomes between countries and individual centers.…”
Section: Discussionsupporting
confidence: 90%
“…Some practices, such as the use of hypothermia in TBI patients, decompressive craniectomy, and ICP monitoring, have been reported to lack efficacy at improving outcomes in preliminary clinical trials. [44][45][46] Nevertheless, our findings are in agreement with multiple observational studies suggesting that the development of specialized neurocritical care unitsusually supported by the presence of neurointensivists and utilizing evidence-based protocols-may contribute to improved patient outcomes. 28 International studies involving neurocritical care patients have suggested that there is considerable variability in outcomes between countries and individual centers.…”
Section: Discussionsupporting
confidence: 90%
“…Most of these evidence-based recommendations are best applied in well-funded and well-equipped neurosurgical or neurotrauma centres [15][16][17] . The recent Benchmark Evidence from South American Trials: Treatment of Intracranial Pressure (BEST Trip) trial was based on standard recommendations for randomized clinical trials in high-income countries [18][19][20][21][22] . Results were far from expected because advanced monitoring tools used to guide treatments in high-income countries were not as successful in LMICs, and discussion within the global neurotrauma scientific community emerged after the publication of this study [23][24][25][26][27] .…”
Section: Epidemiology and Global Research In Tbimentioning
confidence: 99%
“…Thus, for LMICs, the study provided concrete information on which to base resource-allocation decisions, and documented the clinical success of a treatment approach that is sustainable in low-resource environments. Sufficiently skilled clinical staff with a better organized protocol of care could produce good recovery results in the intensive care unit (ICU) without data from an ICP monitor by using clinical assessment to manage intracranial hypertension [53][54][55][56] .…”
Section: Lessons Learned From Clinical Neurotrauma Researchmentioning
confidence: 99%
“…For this reason, interest has grown in developing composite batteries that combine the GOSE with, for example, cognitive tests so as to increase sensitivity and the ability to detect subtle changes in outcome 10 . Composite endpoints have been used in several large-scale clinical trials in TBI, including studies of the impact of magnesium sulphate 67 and intracranial pressure monitoring on functional recovery following TBI 68 . Despite use of a range of outcome measures, these trials still failed to demonstrate benefits of intervention.…”
Section: [H1] Criticismsmentioning
confidence: 99%